The Scope of Legal Protection for Parties in Credit Agreements: A Judicial Review of Decision No. 46/Pdt.g/2022/PN Tpg - Shenti Agustini; Yudhi Priyo Amboro; elza syarief (JURNAL AKTA, 2026)
Credit agreements between banks and debtors are generally made in the form of standard contracts that have accommodated the balance of rights and obligations as required by POJK on consumer protection. Ideally, both creditors and debtors receive equal legal protection. However, Judge’s Decision Number 46/Pdt.G/2022/PN TPG raises a dilemma because the court’s considerations focus only on protecting the debtor as a consumer, while neglecting the creditor’s legal certainty. This study aims to assess the extent to which the decision reflects legal ideals and to analyze the legal protection provided by the judge. Using a normative juridical method with statutory and literature approaches, this research refers to the Civil Code, the Consumer Protection Law, and relevant POJK regulations. The findings show that the decision does not fully embody justice, certainty, or utility, and fails to provide adequate internal or external protection for both parties. Therefore, the study recommends requiring the involvement of heirs in credit agreements and strengthening POJK provisions to ensure balanced legal protection.